2008
DOI: 10.1590/s0102-79722008000300015
|View full text |Cite
|
Sign up to set email alerts
|

Escala de bem-estar afetivo no trabalho (Jaws): evidências de validade fatorial e consistência interna

Abstract: ResumoO objetivo deste estudo foi adaptar uma medida de bem-estar afetivo no trabalho para o contexto brasileiro. Especificamente, pretendeu-se conhecer evidências de validade fatorial e consistência interna da Job-Related Affective Well-Being Scale (JAWS), avaliando se as pontuações nos seus fatores diferem em função do gênero e da idade dos participantes. Participaram 298 trabalhadores de centros comerciais de pequeno e médio porte da cidade de João Pessoa (PB). A maioria destes era do sexo feminino (76,8%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 40 publications
1
6
0
18
Order By: Relevance
“…The results found in Ceará sample are similar to those found in other states of Brazil (e.g Paraiba, Rio Grande do Sul), which have different cultural context. The results showed that all items presented satisfactory discriminative power, corroborating the results indicated by Gouveia, Fonsêca, Lins, Lima & Gouveia (2008) and Lima, Saldanha & Oliveira (2009).…”
Section: Discussionsupporting
confidence: 80%
“…The results found in Ceará sample are similar to those found in other states of Brazil (e.g Paraiba, Rio Grande do Sul), which have different cultural context. The results showed that all items presented satisfactory discriminative power, corroborating the results indicated by Gouveia, Fonsêca, Lins, Lima & Gouveia (2008) and Lima, Saldanha & Oliveira (2009).…”
Section: Discussionsupporting
confidence: 80%
“…Job-Related Affective Well-being Scale -JAWS (Van Katwyk et al, 2000) adapted by Gouveia, Fonsêca, Lins, Lima, and Gouveia (2008). This scale assesses the PA and NA experienced at work.…”
Section: Instrumentsmentioning
confidence: 99%
“…Além da vertente emocional (afetos), o BES inclui uma componente cognitiva, conhecida como satisfação com a vida, que envolve julgamentos globais de satisfação com a vida e com domínios específicos (Gouveia, Fonsêca, Lins, Lima, & Gouveia, 2008;Galinha & Pais-Ribeiro, 2005a). A dimensão cognitiva, os afetos positivos (AP) e os afetos negativos (AN) formam constructos distintos (Diener, Suh, Lucas, & Smith, 1999), mas que se inter-relacionam (Galinha & Pais-Ribeiro, 2005b).…”
unclassified